Blood glutathione concentrations in a large-scale human study - Richie, J P; Skowronski, L; Abraham, P; Leutzinger, Y (Clinical chemistry (Baltimore, Md.), 1996)
Little is known about the variability of blood glutathione (GSH) in human subjects. Thus, we wanted to develop and validate a rapid method for measuring GSH concentrations in whole blood and apply this method to ascertain the variation of GSH in a large-scale study of free-living adults. The assay was highly sensitive (detection limit < 5 pmol) and precise, with an interassay variation of 2.3% and a sampling variation of 3.6%. Applying this method to screen 715 adults, we observed a threefold range of GSH concentrations, with a mean of 1.02 mmol/L and CV of 17%. GSH concentrations were 8-10% greater in smokers than in nonsmokers (P < 0.001). Although we observed no sex differences for GSH, GSH/hemoglobin ratios were 8-18% greater in women < 55 years old than in older subjects (P < 0.05). The results presented here validate the use of this method for large-scale human studies and provide information on the variation and normal values of blood GSH in adults.